RELATIONSHIP BETWEEN ENROLMENT SESSIONS WITH STUDENTS’ ACHIEVEMENT IN ENGINEERING MATHEMATICS 1 - Helley Halen; Adeline Ahyun (Jurnal Penyelidikan Sains Sosial, 2023)
Polytechnic is one of the institutions chosen by students to continue their studies. Because of that, almost all states in Malaysia established Polytechnic branches because of the high demand for these institutions. However, the achievement of students at the Polytechnic is not encouraging. This situation raises the question of whether this is due to the large number of students in one class. Therefore, this study aims to know the relationship between students' enrolment sessions and students' achievement in Engineering Mathematics 1. This research used a quantitative method. The samples were taken from engineering students taking Engineering Mathematics 1 course. The data collected from the result of Engineering Mathematics 1 is based on session 1 and session 2 enrolment. The data were analysed using the Linear Regression test, and the result is p>0.05. A p-value is more than 0.05, meaning no significant relationship existed between the student's enrolment session and Engineering Mathematics 1 achievement. The findings of this study are important to the administration in determining the ideal admission rate